Research Reactions Following Participation in Intimate Partner Violence Research: An Examination With Men in Substance Use Treatment. (November 2016) - Shorey, Ryan C.; Elmquist, JoAnna; Strauss, Catherine; Anderson, Scott E.; Stuart, Gregory L.
There has been increased attention in recent years related to the research reactions of individuals who participate in intimate partner violence (IPV) research. Existing studies demonstrate that participating in IPV research is not emotionally upsetting for the vast majority of participants and that many participants perceive benefit from their research participation. However, almost all of the existing research has utilized non-clinical samples or battered women, failing to examine the research reactions of a clinical sample of men. Thus, the present study examined the research reactions of men in substance use treatment ( N = 138) who completed a self-report measure of IPV perpetration and victimization. We also examined whether distress tolerance moderated the relationship between reports of IPV and negative emotional research reactions. Consistent with previous research, after accounting for distress tolerance, substance use, and demographic control variables, IPV was unrelated to negative emotional research reactions. Distress tolerance did not moderate the association between IPV and research reactions. Findings add to a growing body of literature suggesting that IPV research meets Institutional Review Board (IRB) requirements for minimal risk research.